Modelling of the change in national exchange rate model depending on the economic parameters of a natural gas cogeneration system: Turkey case - Inan, Aslan; Izgi, Ercan; Ay, Selim (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
in this paper, to what extent a cogeneration system's fixed and variable costs and profits are affected from the exchange rate model implemented in the country is examined. An autoproductor system, as known, uses a part of its electrical energy production for its own requirements while selling the remaining energy to the regional energy corporation. As a function of the load factor and the fuel cost, the production cost and energy sale income of the system are influenced much by the exchange rate model of the country. A cost analysis of a natural gas cogeneration (autoproductor) system has been performed for the numerical application, based on the monetary program supported by the IMF commenced in January 2000. In order to investigate the effect of the change in exchange rate model (introducing the floating exchange rate model) on the fuel cost, both the characteristics of the IMF program and some various forecasting methods have been utilized. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Monetary policy; Exchange rate model; Cogeneration; Fuel cost; Inflation; Turkish Lira (TRL); Utilization factor; Thermodynamics; Energy & Fuels; Mechanics